Рассказы про Франца и дедушку - Нестлингер Кристине (Рассказы про Франца, 2017)
Экземпляры: ф.18 (20240311) / Инвентарный номер: 4784 / Цена: / Сис.шифр: 84(4Авс)-4 / Авт.знак: Н 56 / ГРНТИ: 17.82.93 / ББК: 84(4Авс)-44